Open Secrets, Congressional Oversight, and the Geopolitics of the CIA Drone Program - Murphy, Marita C. (2019)
Analyzing four congressional hearings that publicly discuss the CIA’s ‘secret’ drone program, this thesis considers the interaction between publicity and secrecy in facilitating practices of later-modern warfare. Specifically, I examine the content of these drone hearings within the broader context of leaks, Obama administration speeches, and public interest in CIA drones to better understand how open secrecy engages with public oversight. I argue these hearings are deceptively productive. While they largely fail as oversight events, the hearings facilitate numerous unexpected outcomes—including the normalization and entrenchment of the CIA drone program. Paradoxically then, publicity proves essential to the maintenance and acceptance of secret programs. This project concludes by raising questions about the geopolitical implications of the changing spatiality of war when traditional means of oversight and accountability may no longer prove effective